BRAF L485-P490 deletion mutant metastatic melanoma sensitive to BRAF and MEK inhibition: A case report and literature review - Simeng Zhang; Simeng Zhang; Simeng Zhang; Zichang Yang; Zichang Yang; Zichang Yang; Yu Cheng; Yu Cheng; Yu Cheng; Xiaoyu Guo; Xiaoyu Guo; Xiaoyu Guo; et al. (Frontiers Media S.A., 2023)
Background: The combination therapy of BRAF inhibitors (BRAFis) and MEK inhibitors (MEKis) has been approved as a first-line treatment for metastatic melanoma with BRAF V600 mutants. Recently, BRAF mutations have been divided into three subtypes based on biochemical and signaling characteristics. Unlike V600 mutants that show class I BRAF mutations, evidence of the effects of using BRAF inhibitors and MEK inhibitors in patients with non-V600 BRAF mutations remains unclear. The exploration of effective therapy for non-V600 BRAF mutations in melanoma has thus attracted much interest.Case presentation: We reported a case of a 64-year-old female metastatic melanoma patient with a novel BRAF p.L485-P490 deletion mutation. The patient received anti-PD1 agent pembrolizumab (100 mg) therapy as the first-line treatment for two cycles, which was terminated due to an intolerable adverse effect. Considering the p.L485-P490 deletion mutation signal as an active dimer which is akin to a class II BRAF mutation, the patient underwent dabrafenib and trametinib combination therapy as a second-line treatment. After two cycles of combination treatment, the patient achieved a partial response confirmed by radiological examinations. At the last follow-up date, the patient had obtained over 18 months of progression-free survival, and the treatment was well tolerated.Conclusion: The combination therapy of dabrafenib and trametinib has been proven to be an effective method as a later-line therapy for metastatic melanoma patients with class II BRAF in-frame deletion mutations.